Evaluation of micro-parallel liquid chromatography as a method for HTS-coupled actives verification. - Simeonov, A; Yasgar, A; Klumpp, C; Zheng, W; Shafqat, N; Oppermann, U; Austin, C; Inglese, J (2007)
The identification of biologically active compounds from high-throughput screening (HTS) can involve considerable postscreening analysis to verify the nature of the sample activity. In this study we evaluated the performance of micro-parallel liquid chromatography (microPLC) as a separation-based enzyme assay platform for follow-up of compound activities found in quantitative HTS of two different targets, a hydrolase and an oxidoreductase. In an effort to couple secondary analysis to primary screening we explored the application of microPLC immediately after a primary screen. In microPLC, up to 24 samples can be loaded and analyzed simultaneously via high-performance liquid chromatography within a specially designed cartridge. In a proof-of-concept experiment for screen-coupled actives verification, we identified, selected, and consolidated the contents of "active" wells from a 1,536-well format HTS experiment into a 384-well plate and subsequently analyzed these samples by a 24-channel microPLC system. The method utilized 0.6% of the original 6-microl 1,536-well assay for the analysis. The analysis revealed several non-biological-based "positive" samples. The main examples included "false" enzyme activators resulting from an increase in well fluorescence due to fluorescent compound or impurity. The microPLC analysis also provided a verification of the activity of two activators of glucocerebrosidase. We discuss the benefits of microPLC and its limitations from the standpoint of ease of use and integration into a seamless postscreen workflow.